Communication Patterns Between Institutions and the Families of First-Generation College Students: A Multiple Case Study. Issue 2 (4th May 2022) - Harper, Casandra E.; Kiyama, Judy M.; Lee, Alice Eunjung
ABSTRACT: This article explores how higher education institutions are engaging and communicating with the parents and families of first-generation college students. Drawing on multiple case study data from families and staff members within a multi-year project on parent and family engagement, this article identifies what communication parents and families are receiving from institutions, how parents and staff perceive that communication, barriers to communication, and why increased communication might be desired and beneficial to first-generation college students and their families. We address communication practices between parents and institutions and find five patterns: absent, insufficient, indirect, direct–parent initiated, and direct–university initiated.